GRAVES DISEASE - Prettysun Ang Mellow (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2023)
Graves' disease is one of the most common autoimmune diseases. The disease is named after the scientist Robert James Graves, who first described it in the 19th century as a syndrome with an enlarged and overactive thyroid gland (hyperthyroidism due to circulating autoantibodies), rapid heart rate, and eye abnormalities. graves’ disease is the most common cause of hyperthyroidism and affects more women than men. Graves’ disease can appear at any age, but it most commonly appears for the first time between the ages of 20 and 40. Factor is a predisposition that is more dominant than environmental factors. There are circulating autoantibodies produced by B lymphocytes induced by autoreactive T lymphocytes that recognize thyrotropin-stimulating hormone (TSH) receptors in thyroid tissue as self-antigens. These autoantibodies are also known as TSH receptor antibodies (TSH-R Ab), thyrotropin stimulating antibodies (TSI), or thyrotropin receptor antibodies (TRAb). TRAb acts like TSH to cause thyroid hyperplasia (diffuse goitre), increased synthesis, and excessive and uncontrolled secretion of thyroid hormones (T4: tetraiodothyronine T4 and T3: triiodothyronine T3). Investigations to confirm Graves’ disease show elevated thyroid hormones (T4 and T3) with very low TSH and increased TRAb. On thyroid ultrasound, the majority of patients have a hypervascular and hypoechoic diffusely enlarged thyroid gland. The treatment for graves’ disease is to reduce the synthesis of thyroid hormones using anti-thyroid drugs, or to reduce the amount of thyroid tissue with radioactive iodine (RAI) or total thyroidectomy. Methimazole is the first-choice antithyroid drug with good effectiveness and safety. Although the recurrence rate after stopping the drug is still quite high